Stem cell therapy for female stress urinary incontinence: Results, limitations and lessons learned from a pilot clinical study - Rodrigo C. Souza; Maria A. T. Bortolini; Yasmin Melino; Juliana A. P. de Godoy; Kelen Alvarez; Denise De Oliveira; Andrea T. Kondo; Jose M. Kutner; Mariane Secco; Eder Zucconi; Natássia Vieira; Sérgio Podgaec; et al. (PLoS ONE, 2026)
Objective This pilot clinical study aimed to develop and validate standardized manufacturing and quality control procedures for autologous skeletal muscle-derived (SkM-MSCs) and bone marrow-derived mesenchymal stem cells (BM-MSCs), and to explore the feasibility, safety and preliminary efficacy of periurethral injection of these products in women with stress urinary incontinence (SUI). Methods Twenty-six diagnosed with SUI were enrolled and allocated to receive either SkM-MSCs or BM-MSCs. Autologous MSCs were isolated from skeletal muscle or bone marrow biopsies, expanded under Good Manufacturing Practices (GMP), and subjected to rigorous quality control assessments, including identity, genetic stability, viability, potency, and sterility. In this pilot study, ten million MSCs were injected periurethrally under local anesthesia, and participants were followed for 12 months post-treatment. Results Eleven SkM-MSCs and nine BM-MSCs final products met all quality criteria and were administered. One participant from the SkM-MSCs lost the follow-up. MSC therapies were well tolerated, with no long-term adverse effects or tumor formation observed. In the SkM-MSCs group, the proportion of women with a positive cough test decreased significantly from 100% to 40% (p = 0.010). In the BM-MSCs group, modest improvements were seen but did not reach statistical significance. Overall, improvements in both pad test outcomes and quality of life measures among participants were observed, though not uniformly significant. The study was discontinued before reaching its intended sample size due to limited efficacy, logistical challenges, and financial constraints. Conclusion Autologous MSC‑based therapy for SUI was feasible and showed an acceptable short‑term safety profile in this pilot research setting; however, clinical efficacy remained modest. The manufacturing and quality control methodology is reproducible in specialized cell processing centers, but its application should remain confined to clinical research conducted in compliance with current regulations governing human cell therapy. Future studies with optimized cell products, refined delivery strategies and adequately powered, randomized designs are required before any potential translation to routine clinical practice can be considered.